KETIDAKMATANGAN PSIKOLOGIS TOKOH LANA DAN RENO DALAM NOVEL DREAM PARTNER KARYA NDA QUILLA: ANALISIS PSIKOLOGI SASTRA - Zahro, Tsania Safiratuz; Sumartini (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This article analyzes the psychological immaturity of the characters Lana and Reno in the novel Dream Partner by Nda Quilla through a literary psychology approach. The analysis applies the psychoanalytic theory of Sigmund Freud to examine the personality structures of the id, ego, and superego as represented in the characters’ dialogue, narration, and actions, using a descriptive qualitative method with reading and note-taking techniques applied to relevant textual data. The findings reveal an imbalance in the personality structure, marked by the dominance of the id in impulsive behavior and unstable emotions, a weak ego in adapting to the realities of marriage, and a developing superego that functions as moral pressure, generating guilt and anxiety. These conditions are influenced by age, emotional experience, premarital pregnancy, as well as social and economic pressures. This study broadens the scope of literary psychology by positioning Dream Partner as an object of psychoanalytic analysis to examine the relationship between disharmony in personality structure and the dynamics of domestic conflict, offering a new perspective on character formation and development in contemporary popular fiction through Freud’s structural theory of personality.